Memória humana e teatro - Alves, Edna De Souza [UNESP]; Alves, Marcos Antônio [UNESP] (Universidade Estadual Paulista, Departamento de Filosofia, 2001)
The human memory plays an essential role in theatrical activity because it makes it possible that the actors record their lines and the public understands the message transmitted in the play. In this work, the notion of memory proposed by Descartes, Hume and Kohonen are investigated. For those thinkers, memory is indispensable to obtain and develop knowledge. In our opinion, the study of memory is of great importance for the theater, because the theater doesn't exist without memory.

A memória humana é essencial para a atividade teatral. Isso por um motivo óbvio: é ela que possibilita aos atores gravarem suas falas e ao público compreender a mensagem passada pela peça. Neste trabalho, investigamos as noções de memória propostas por Descartes, Hume e Kohonen. Para eles, a memória é imprescindível na obtenção e desenvolvimento do conhecimento. A nosso ver, o estudo da memória é de grande importância para o teatro, à medida que este não seria possível sem aquela.
Human memory and theater
Keywords: Human memory; theater; knowledge; Memória humana; teatro; conhecimento